IDENTIFYING JOB STRESSORS AMONG THE MANAGERIAL AND NONMANAGERIAL EMPLOYEES IN THE MANUFACTURING SECTOR - Barboza, Ms Coral; Thomas, Dr Babu (IJRDO - Journal of Applied Management Science, 2017)
Stress, since ancient times is known to be studied in different areas. In the field of engineering, stress is studied as a force which deforms bodies. In Biology and medicine, it refers to a process in the body, to the body’s general structure for adapting to all the influences, changes, demands and strains to which it might be exposed. There is something common in these cases in the way the body attempts to change or adapt. This common denominator according to Selye (1971), is a kind of revving up is stress. Stress is, then, a stereotype in the body’s responses to generally speaking, influences, demands or strains. In this paper, the researcher tries to find out the various kinds of stressors the managerial and non-managerial employees face in the manufacturing sector in Mangalore city with a sample size of 80 respondents. At times the reactions of the respondents are pleasant, sometimes unpleasant; sometimes useful, sometimes doing harm. It is seen from the findings of the study that the non-managerial employees face more job stress compared to the managerial level of employees.